183k views
5 votes
Given the exponential function g(x) = 12(2⁄3)x, find g(0) and g(1).

A. g(0) = 12; g(1) = 8
B. g(0) = 12; g(1) = 51⁄3
C. g(0) = 8; g(1) = 51⁄3
D. g(0) = 8; g(1) = 12

User NikzJon
by
5.9k points

2 Answers

6 votes

Answer:

The Answer is A

Explanation:

1. g(0) means that we need to replace X by 0 in the given function. For the other case, g(1) means we need to replace X by 1 in the given function.

2. For the first case we have


g(0)= 12 ((2)/(3) )^ 0 =12(1)=12

note: remember any number raised to the 0 is 1

3. For the second case we have


g(1)=12((2)/(3) )^1=12(2/3)= (24)/(3)=8

note: remember any number raised to 1 yields the same number.

User Ackdari
by
5.9k points
5 votes

Answer:

A g(0) =12 g(1) = 8

Explanation:

g(x) = 12(2⁄3)^x

g(0) means x=0

g(0) = 12(2⁄3)^0

=12 (1) = 12

g(1) means x=1

g(1) = 12(2⁄3)^1

=12 (2/3)

=24/3 = 8

User Fred Pym
by
6.4k points